Primeros registros y confirmación de la Paloma Plomiza (Patagioenas plumbea) en la Argentina - Pearman, Mark; Zambrano, Marcelo; Bodrati, Alejandro (Nuestras Aves, 2011)
Este artículo no cuenta con un resumen.